Revitalization of National Values in Learning at Sekolah Kebangsaan Dato' Wan Ahmad Rasid Malaysia - Sam'un Mukramin; Lukman Ismail; St. Haniah; Fatmawati Rahim; Yang Sharkawi bin Shaharum (Yayasan Keluarga Guru Mandiri, 2025)
Education plays a strategic role in revitalizing national values to ensure their relevance for the younger generation. This study aims to analyze the efforts made to revitalize national values in the learning process at Sekolah Kebangsaan Dato' Wan Ahmad Rasid, Malaysia. Employing a qualitative approach with a case study method, data were collected through interviews, participant observation, and document analysis. Data were analyzed using data reduction techniques, data presentation, and conclusion drawing, with the validity ensured through triangulation of sources and methods. The findings reveal that national values are revitalized through curriculum integration, experiential learning methods, and the use of digital technology. Extracurricular programs and community engagement significantly reinforce students' national identity. The study identifies several challenges, including the effects of globalization, changing mindsets among the younger generation, and the limited use of innovative teaching methods. The study proposes strengthening value-based education, integrating technology in pedagogy, and enhancing parental and community involvement to address these challenges. This study contributes to developing an adaptive and contextual model for national value education and serves as a valuable reference for educational institutions in designing more effective strategies to instill national values in the modern era.